2022
DOI: 10.1186/s12915-021-01203-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of co-isogenic prion protein deficient mice reveals behavioral deficits, learning impairment, and enhanced hippocampal excitability

Abstract: Background Cellular prion protein (PrPC) is a cell surface GPI-anchored protein, usually known for its role in the pathogenesis of human and animal prionopathies. However, increasing knowledge about the participation of PrPC in prion pathogenesis contrasts with puzzling data regarding its natural physiological role. PrPC is expressed in a number of tissues, including at high levels in the nervous system, especially in neurons and glial cells, and while previous studies have established a neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Altogether, our partnership with medical teams provided answers to difficult humanlevel explorations or preliminary results for future human therapies. Our compromise is strong and, in addition to Parkinson's disease and the above physicochemical actions, we have contributed to advance biomedical questions in Sanfilippo [30], Huntington's disease [25,26,31], Alzheimer's disease [14], and cellular prion pathogenesis [32]. From left to right, data correspond to a healthy culture, a culture derived from cells affected by a genetic form of PD, and a culture whose cells were genetically-edited to correct for the disease.The PD culture exhibits an excessive integration, with stronger synchronization in the raster plots and bigger communities; (b) recovery of an aggregated culture after laser microsurgery (yellow spot before damage, black spots after it).…”
Section: The Study Of Neurological Disorders In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, our partnership with medical teams provided answers to difficult humanlevel explorations or preliminary results for future human therapies. Our compromise is strong and, in addition to Parkinson's disease and the above physicochemical actions, we have contributed to advance biomedical questions in Sanfilippo [30], Huntington's disease [25,26,31], Alzheimer's disease [14], and cellular prion pathogenesis [32]. From left to right, data correspond to a healthy culture, a culture derived from cells affected by a genetic form of PD, and a culture whose cells were genetically-edited to correct for the disease.The PD culture exhibits an excessive integration, with stronger synchronization in the raster plots and bigger communities; (b) recovery of an aggregated culture after laser microsurgery (yellow spot before damage, black spots after it).…”
Section: The Study Of Neurological Disorders In Vitromentioning
confidence: 99%
“…In partnership with different research institutes in medicine, we have helped investigating the goodness of cell therapies, e.g., gene editing or transplantation, as well as the potential use of new chemical compounds as pharmacological agents. See Refs [14,20,[25][26][27][28][29][30][31][32]…”
mentioning
confidence: 99%
“…In contrast to Huntingtin, Prnp null mutants are viable and a variety of Prnp knock-out models have been generated [58][59][60] . However, these mice show diverse phenotypic variations, which has led to a variety unrelated of roles being attributed to PrP c , including involvement in phagocytosis of apoptotic cells 61 , involvement in synaptic function 62,63 , and myelin homeostatsis 64 . It was later found that several of these effects may instead originate from genes flanking the Prnp locus and co-segregating with Prnp.…”
Section: The Prion Proteinmentioning
confidence: 99%
“…Most recently, the N-terminal copper-binding site of PrP C was demonstrated to be essential for neuronal protection and neuritogenesis (Nguyen et al 2019 ). In addition, to overcome the issue with genetic artefacts associated to lack of proper PrP C knockout models in several of the PrP C functions indicated above, a more physiologically relevant co-isogenic Prnp 0/0 mouse model ( Prnp ZH3/ZH3 ) was developed (Matamoros-Angles et al 2022 ; Nuvolone et al 2016 ). The co-isogenic PrP C knockout model studies demonstrated a vital role in peripheral myelin maintenance, neural network formations, synaptic regulations and cognitive abilities (Matamoros-Angles et al 2022 ; Nuvolone et al 2016 ).…”
Section: Prp C Structure Biogenesis and Physiologi...mentioning
confidence: 99%
“…In addition, to overcome the issue with genetic artefacts associated to lack of proper PrP C knockout models in several of the PrP C functions indicated above, a more physiologically relevant co-isogenic Prnp 0/0 mouse model ( Prnp ZH3/ZH3 ) was developed (Matamoros-Angles et al 2022 ; Nuvolone et al 2016 ). The co-isogenic PrP C knockout model studies demonstrated a vital role in peripheral myelin maintenance, neural network formations, synaptic regulations and cognitive abilities (Matamoros-Angles et al 2022 ; Nuvolone et al 2016 ). Thus, multiple functions of PrP C suggest that the abnormal conformation due to conversion into PrP TSE generates potential disturbances in various biological processes leading to pathogenesis in PrD.…”
Section: Prp C Structure Biogenesis and Physiologi...mentioning
confidence: 99%